Entrepreneurship, Performance, and Welfare: Role of Village-Owned Enterprise's Resources and Social Capital - Sinarwati, Ni Kadek; Sri Budhi, Made Kembar; Utama, Made Suyana; Marhaeni, Aain (Faculty of Economics and Business, Universitas Negeri Yogyakarta in collaboration with the Institute for, 2025)
AbstractResearch on the determinants of entrepreneurship and performance of micro-small business actors (MSEs) has been carried out, but research on the role of entrepreneurship and performance on the welfare of MSE actors is limited. This study analyzes the role of BUMDes resources and social capital on Artisans' entrepreneurship, performance, and welfare. Data were collected by observation, questionnaires, and in-depth interviews and analyzed using Partial Least Square. The results show that BUMDes resources have not played a role, while social capital has been proven. The implications of research on BUMDes management and Village Community Empowerment Institutions must further introduce the existence of BUMDes. This will increase the interaction of BUMDes managers with the village community. The Ministry of Industry and Trade should work together to create an association of artisans of export products. The next researcher is advised to examine the role of the government.